Removal of lycopene substrate inhibition enables high carotenoid productivity in Yarrowia lipolytica - Yongshuo Ma; Nian Liu; Per Greisen; Jingbo Li; Kangjian Qiao; Sanwen Huang; Gregory Stephanopoulos (Nature Communications, 2022)
Substrate inhibition has not been widely studied in the context of synthetic biology and metabolic engineering. Here, the authors report removal of lycopene substrate inhibition by two different strategies and enable high carotenoid productivity in Yarrowia lipolytica.